Address before the Foreign Policy Association, Minneapolis, January 19, 1949 - McCloy, John J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, spoke about the elusive matter of international economic recovery. He reviewed the policy environment for the European Recovery Program (Marshall Plan), economic integration, and international trade imbalances. Europe’s dollar problem is America’s dollar problem.